Developing a work/study programme for midwifery education in East Africa. - Edwards, Grace; Hellen, Kyakuwaire; Brownie, Sharon (Midwifery, 2018)
Background there is extensive evidence to show that skilled midwifery care is crucial in reducing maternal deaths; however, in East Africa, the midwifery profession has been subsumed within the nursing role. This paper highlights issues in the preparation of skilled midwives in three East African countries, specifically, Uganda, Kenya and Tanzania and provides a case study description of a flexible work/study programme designed to develop skilled midwives to meet internationally regarded ICM competency standards in midwifery education and practice. The model a flexible, competency-based Bachelor's of Science in Midwifery programme (BScM) has been developed based on fifteen years' experience of running a Bachelor of Science in nursing programme. The new BSCM programme allows licensed diploma midwives the opportunity to study for two days a week towards a bachelor's degree in midwifery, whilst continuing to work and support their families. The model also provides education at degree level thus providing a sound platform for ongoing development of a cadre of midwifery leaders. Conclusion the BScM education model for working midwives builds on the success of the BScN work/study model in developing strong leadership, clinical and critical thinking competencies. The newly developed midwifery programme provides a pathway by which to increase the availability of skilled East African midwives educated to the Global Standards for Midwifery Education.